2014
DOI: 10.1128/jvi.03194-13
|View full text |Cite|
|
Sign up to set email alerts
|

Development of an Adenovirus-Based Respiratory Syncytial Virus Vaccine: Preclinical Evaluation of Efficacy, Immunogenicity, and Enhanced Disease in a Cotton Rat Model

Abstract: The lack of a vaccine against respiratory syncytial virus (RSV) is a challenging and serious gap in preventive medicine. Herein, we characterize the immunogenicity of an adenovirus serotype 5-based RSV vaccine encoding the fusion (F) protein (Ad5.RSV-F) and the protection provided following immunization with Ad5.RSV-F and assess its potential for producing enhanced disease in a cotton rat (CR) model. Animals were immunized intranasally (i.n.) and/or intramuscularly (i.m.) and subsequently challenged with RSV/A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 40 publications
3
17
0
Order By: Relevance
“…A similar result, i.e. effective protection from challenge in the lung but persistent RSV in the upper respiratory tract, was also observed in cotton rats vaccinated intra-muscularly with a single dose of up to 10 11 viral particles of a recombinant replication-defective adenovirus vaccine (Kim et al, 2014;Widjojoatmodjo et al, 2015). Interestingly, a single dose of the same vaccine administered intra-nasally resulted in a more robust protection, further supporting the hypothesis that local immunity is an important determinant of protection that future vaccine strategies should consider.…”
Section: Groupssupporting
confidence: 70%
“…A similar result, i.e. effective protection from challenge in the lung but persistent RSV in the upper respiratory tract, was also observed in cotton rats vaccinated intra-muscularly with a single dose of up to 10 11 viral particles of a recombinant replication-defective adenovirus vaccine (Kim et al, 2014;Widjojoatmodjo et al, 2015). Interestingly, a single dose of the same vaccine administered intra-nasally resulted in a more robust protection, further supporting the hypothesis that local immunity is an important determinant of protection that future vaccine strategies should consider.…”
Section: Groupssupporting
confidence: 70%
“…Significant levels of F protein were identified in HEp-2 cells using ELISA and immunofluorescence with a higher abundance of the secretory form. The proper expression of these constructs is consistent with the previous trials of DNA immunization using codon optimized and truncated F protein forms 17,23,26,37 It was expected that the secretory form should have the lowest intracellular concentration due to its rapid secretion in the cell supernatant. Harvesting the expressed proteins 48 hr posttransfection, which may be insufficient for protein secretion, can justify this unexpected finding.…”
Section: Discussionsupporting
confidence: 56%
“…11 The F protein was highly recommended for use in the development of vaccine candidates due to its conserved nature and ability to induce neutralizing antibodies and cytotoxic T lymphocytes. 12,13 A number of HRSV vaccine candidates were generated and tested in preclinical and/or clinical trials including FI-RSV, 14 live-attenuated, 15 subunit 16 and viral vector-based 17 vaccines. FI-RSV was prohibited due to its hazardous effect, which resulted in disease enhancement and the death of 2 vaccine recipients.…”
Section: Introductionmentioning
confidence: 99%
“…We chose a dose of 2x10 5 PFU that was recently reported to be sufficient to assess the efficacy of RSV vaccines (Garg et al, 2014; Johnson et al, 2014; Kim et al, 2014; Murata and Catherman, 2012; Nguyen et al, 2012; Schmidt et al, 2012). We also found that the PBS or PR8 WT group of mice that were infected with 2x10 5 PFU RSV showed a high titer of approximately up to 10 4 PFU from lungs at day 5 post infection (Fig.…”
Section: Resultsmentioning
confidence: 99%